2016
DOI: 10.1021/acs.jpcc.6b09505
|View full text |Cite
|
Sign up to set email alerts
|

Ni Substitutional Defects in Bulk and at the (001) Surface of MgO from First-Principles Calculations

Abstract: Computational detailsCCSD(T) calculations of CO, CO 2 , and H 2 adsorption energies at Ni Mg defects at the MgO(001) surface, as well as formation energies of bulk Ni Mg , are performed using ORCA electronic-structure package, which is based on Gaussian-type orbitals [1]. For bulk Ni Mg defects, NiMg 12 O 6 (PP) 50 cluster is used (Fig. 1c in main ). 14 electrons are removed to ensure bulklike ionization states of all the atoms. The positions of the atoms, ECPs, and point charges in the bulk cluster models ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 72 publications
(158 reference statements)
6
36
0
Order By: Relevance
“…A Ni surface enrichment of the solid solutions is observed, by both physical and chemical analysis methods, in agreement with the prediction made from first principle calculations. 24 This enrichment somehow has its restrictions, as samples containing 10 atom % Ni or more show a saturation phenomenon. These Ni single atom catalysts are active for CO 2 activation in the reverse-water–gas-shift reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Ni surface enrichment of the solid solutions is observed, by both physical and chemical analysis methods, in agreement with the prediction made from first principle calculations. 24 This enrichment somehow has its restrictions, as samples containing 10 atom % Ni or more show a saturation phenomenon. These Ni single atom catalysts are active for CO 2 activation in the reverse-water–gas-shift reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The validation of this method is shown in our previous work. 24 We have used the FHI-aims code, 25 which is all-electron with numerical atomic orbitals. The “tight” 25 numerical settings and basis sets were employed.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that carbon dioxide adsorption energies and, thus, formation energies of surface carbonates have high values on lowcoordinated sites (steps, corners, etc.) [43]. The strongest binding of single CO2 molecules occurs on step sites with reported adsorption energy about 2.54 eV.…”
Section: Discussion and Mechanistic Interpretationmentioning
confidence: 99%
“…S5.3b-d). This may indicate the desorption of carbon dioxide from more basic surface sites of MgO such as steps or corners [43].…”
Section: T Dec Last Co2 T Dec 1st Co2 T Dec Last Co2 T Dec 1st Co2 T ...mentioning
confidence: 99%
“…Furthermore, choosing arbitrarily the H 2 :Ni stoichiometric factor or hydrogen activation and spillover phenomena (that can occur on the support) can also distort the results [15,56]. In that context, MgO may exhibit such effects as experimental and theoretical studies have shown that MgO has the ability to undergo direct adsorption and dissociation of H 2 [57]. Besides, it could diffuse into the subsurface layers and into the bulk sites [58][59][60][61].…”
Section: B) A)mentioning
confidence: 99%